Examination of money supply endogeneity in Turkey: Evidence from asymmetric causality test - Dincer Dedeoglu; Kaan Ogut (Cogent Economics & Finance, 2018)
In this study, we examine the money supply endogeneity in Turkish economy for the post crises period, between 2009.10 and 2016.12 by employing asymmetric causality test. Our results reveal that a positive credit shock will cause a positive shock in the money supply. That is, an increase in banking sector credit volume will cause an increase in money supply. However, such a causal impact for negative shocks is not found. Our findings show that the causality runs from bank loans to money supply for the positive components so credit cuts may not initiate a fall in money supply.
Keywords: 330; Money supply endogeneity; granger causality; asymmetry